The role of cognitive biases and negative life events in predicting later depressive symptoms in children and adolescents - Platt, Belinda; Sfärlea, Anca; Löchner, Johanna; Salemink, Elske; Schulte-Körne, Gerd (Journal of Experimental Psychopathology, 2023)
Aims: Cognitive models propose that negative cognitive biases in attention (AB) and interpretation (IB) contribute to the onset of depression. This is the first prospective study to test this hypothesis in a sample of youth with no mental disorder. Methods: Participants were 61 youth aged 9–14 years with no mental disorder. At baseline (T1) we measured AB (passive-viewing task), IB (scrambled sentences task) and self-report depressive symptoms. Thirty months later (T2) we measured onset of mental disorder, depressive symptoms and life events (parent- and child-report). The sample included children of parents with (n = 31) and without (n = 30) parental depression. Results: Symptoms of depression at T2 were predicted by IB (ß =.35, p =.01) but not AB (ß =.05, p =.72) at T1. This effect was strongest for children who experienced multiple negative life events (F2,48 = 6.0, p =.018, ΔR2 =.08). IB did not predict depressive symptoms at T2 over-and-above the effect of depressive symptoms at T1 (ß =.21, p =.13). Discussion: These findings suggest that IB (but not AB) plays an important role in the aetiology of depression. Modifying IB may have a preventive effect on youth depression, particularly for youth who experience negative life events. This prospective study provides important foundations for future experimental studies.
CRIS-Team Scopus Importer:2024-11-26
Keywords: attention; interpretation; parental depression; stress; youth